PHRASEOLOGY - A WAY OF KNOWING A PERSON (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This scientific article is devoted to the study of phraseological equivalents in Russian and Uzbek languages and examines phraseological units and phraseological turns. Their classification and definitions are considered.